Endoscopic Endonasal Transmaxillary Transpterygoid Approach to Meckel Cave: Anatomical Study and Preliminary Clinical Results - Gu, Ye; Yu, Yong; Zhang, Xiaobiao; Hu, Fan; Wang, Xuejian; Xu, Wenlong; Xie, Tao (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Objective Tumors involving Meckel cave (MC) always present challenges to neurosurgeons. We performed an investigation of the anatomical characteristics of the endoscopic endonasal transmaxillary transpterygoid approach to MC as an alternative to routine transcranial approaches and further confirmed its efficacy in the clinical setting.Methods Five adult fresh head specimens (10 sides) were studied to identify crucial anatomical landmarks and quantify the anatomical structures involved in the endoscopic endonasal transmaxillary transpterygoid approach. Two patients with a tumor involving the left MC were treated using the endoscopic endonasal transmaxillary transpterygoid approach.Results The distance from the columella nasi to the choana, the sphenoid ostium, the anterior aperture of the palatosphenoidal canal (PSC), the sphenopalatine foramen, and the anterior aperture of the vidian canal (VC) was 66.5 ± 3.3 mm, 61.2 ± 1.6 mm, 64.6 ± 1.4 mm, 62.8 ± 2.3 mm, and 75.4 ± 3.3 mm, respectively. The distance from the anterior aperture of the VC to the anterior aperture of the PSC and the foramen rotundum (FR) was 2.1 ± 0.7 mm and 7.5 ± 0.7 mm, respectively; the length of the PSC and the VC was 6.4 ± 0.5 mm and 13.3 ± 1.2 mm, respectively. The landmarks of this route included the PSC, the VC, and the paraclival carotid prominence (CP). Subtotal resection and gross total resection were achieved in the first and second patients, respectively.Conclusion The anatomical landmarks of the endoscopic endonasal transmaxillary transpterygoid route are useful for clinical application. The endoscopic endonasal transmaxillary transpterygoid approach is an effective and minimally invasive route for certain tumors involving MC. Identifying the anatomical landmarks including the PSC, the VC, the FR, and the CP is crucial for safe manipulation.
Keywords: endoscopy; endonasal transmaxillary transpterygoid approach; anatomy; Meckel cave; tumor